A produção do urbano e a (re)produção de desigualdades: a COVID-19 nos assentamentos precários de Curitiba - Pontes, Alana Figueiredo (2023)
The world currently lives a scenario of uncertainty facing the consequences of the emergence of the new Coronavirus (Sars-Cov-2), which, spreading throughout the world, caused, in 2020, the beginning of the pandemic of COVID-19. As Brazil is a country known for its strong sócio-spatial inequalities and its urban construction resulting in an excluding space, it is observed that the pandemic has the potential to impact differently on its various territories, thus resulting in the possibility of a greater exposure of a certain portion of the population to greater risks and contingencies. Taking as a case study the city of Curitiba, this research seeks to analyze whether the COVID-19 affects disproportionately territories marked by precariousness, especially in aspects of income, housing and access to public services. From the spatialization of data from the Municipal Health Secretariat for the cases of contamination and death confirmed by COVID-19, from the analysis of socioeconomic data and from the territorialization of precarious settlements and housing developments in the city, it appears that, in comparison with other capitals with higher rates of social inequality and greater precariousness, Curitiba, by presenting better indicators of public health, sanitation and quality of homes, does not present in a discrepant way the worsening of the pandemic in precarious territories, despite the concentration of cases in peripheral neighborhoods. In this sense, along with the risk factors related to housing, the factors related to health, such as age, are more linked to the concentration of deaths and the lethality rate of the disease itself, since there is a certain decrease in the contingent of elderly people in peripheral areas. The research also highlights the importance of the quality of spatial information of the data collected, especially by public health agencies to enable the monitoring and public action in the most precarious areas of the city to face the pandemic, precisely because of its ability to catalyze the transmission of the disease.